Partisan alignment and political corruption: Evidence from a new democracy - Alexander Stöcker (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2021)
I analyze the link between partisan alignment of local politicians and the incidence of political corruption, using novel hand-collected data on local political corruption in Ghana. In line with political ambition theory, I hypothesize that local politicians aligned with the national government have incentives to control fiscal irregularities within their localities in order to appease their national party leaders and preserve their party's reputation. The empirical analysis, based on 205 districts observed over the period 2013-2018, indeed suggests significantly lower levels of political corruption in aligned districts. Partisan alignment reduces corruption by 2.0 percentage points, equivalent to roughly 50 percent of the 3.9 percent mean-level of non-aligned districts. This effect is more pronounced in districts with (i) less competitive local legislative elections, (ii) better financial endowments, and (iii) female local parliamentarians. It appears that high levels of political polarization and intense party competition, as observed in Ghana, are important explanations for this finding.
Keywords: 330; corruption; political alignment; local public finance; intergovernmental transfers; political career concerns; Africa